Wordwall interactive learning model for Mathematics subject in elementary school - Nopiyanti, Rima; Dewi, Muharika (PT The Collaboration UVW, 2024)
This research aimed to determine students' needs in the learning process in Mathematics subjects. Data collection used a needs analysis questionnaire for class VI SD N 095/VIII Karang Dadi students. The results of the analysis of student needs showed that the interest aspect was 86% in using learning media Wordwall with the high category and the results of needs aspect were 86% in the high category. So that, the interactive learning media Wordwall can help students understand the material presented by the teacher.